PEREMPUAN DALAM TAFSIR FATIMA MERNISSI - Elya Munfarida (MAGHZA, 2016)
This paper is study about congregate Islamic Arabia with colonialism which instinctive many response among Islamic scholars defensively or accommodative. The accommodative response within variants ,one isÂ  accommodate the product of modern scholars , other sideeven accommodative but still carry on the Islamic tradition. One of the African scholar who is accommodative is Fatima Mernissi. She is feminist from maroco who is concern on women studies. Based on her worry about social reality of women in Islam whom have been getting sub ordinance and discrimination in the patriarchy culture stronger in Islamic society, she struggle by interpretation of text of religion which is center of attention on women. In her interpretation,she tried to integrate Islamic tradition and feminism theories. Islam, according to her, is very appreciate with women existence which is imagined have equal position in religion and social base on value of equal universal humanity in which discovery in the text of religion. Agency of women relate to ability in making determinate and independence in the social and sexual relation that verified in the history of prophet.